Control of ALS- and EPSPS-Resistant Amaranthus palmeri by Alternative Herbicides Applied in PRE- and POST-Emergence - GONÇALVES NETTO,A. (2019)
ABSTRACT: The emergence of resistant biotypes of the Amaranthus palmeri species in cotton production areas of the state of Mato Grosso, Brazil, generated the need for correct identification of this species and information on viable herbicidal tools for their management. Thus, greenhouse experiments were conducted to evaluate the efficacy of alternative herbicides applied to A. palmeri in pre and post emergence. A randomized block design with four replications was used. The efficacy of herbicides applied in pre emergence was evaluate in two experiments, one in a clayey and other in a sandy soil; 9 herbicide treatments (8 with herbicide application and a control without application) were applied on each soil. Subsequently, two experiments with different populations of A. palmeri were conducted, using a 13 x 2 factorial arrangement, to evaluate the efficacy of herbicides applied in post emergence. The factors consisted of 13 herbicide treatments (12 with herbicide application and a control without application) and two weed development stages (2-4 and 6-8 leaves). Pre-emergence application of the flumioxazin, S-metolachlor, isoxaflutole, and trifluralin herbicides controlled the weed satisfactorily in both evaluated soils. The sulfentrazone and metribuzin herbicides were effective in the sandy soil, and diuron was effective in the clayey soil. The clomazone herbicide did not successfully controlled the A. palmeri plants in any of the soils. All post-emergence herbicide treatments were effective for the management of A. palmeri plants, when they were applied at the 2-4 leaf stage.